Effect of an automated flexible endoscope channel brushing system on improving reprocessing quality: a randomized controlled study - Shang, Renduo; Liu, Jun; Luo, Zi; Huang, Xingmin; Zhang, Caiqing; Chen, Di; Wu, Lianlian; Yao, Liwen; Wang, Xianglan; Wang, Qing; Wu, Yunxing; Zhang, Lili; Yu, Honggang (Endoscopy, 2023)
Background Qualified reprocessing, of which meticulous channel brushing is the most crucial step, is essential for prevention and control of endoscopy-associated infections. However, channel brushing is often omitted in practice. This study aimed to evaluate the effect of an automated flexible endoscope channel brushing system (AECBS) on improving the quality of endoscope reprocessing.Methods This prospective, randomized controlled study was conducted between 24 November 2021 and 22 January 2022 at Renmin Hospital of Wuhan University, China. Eligible endoscopes were randomly allocated to the auto group (channels brushed by AECBS) or the manual group (channels brushed manually), with sampling and culturing after high-level disinfection and drying. The primary end point was the proportion of endoscopes with positive cultures.Results 204 endoscopes in the auto group and 205 in the manual group were analyzed. The proportion of endoscopes with positive cultures was significantly lower in the auto group (15.2 % [95 %CI 10.7 %–21.0 %]) than in the manual group (23.4 % [95 %CI 17.9 %–29.9 %]).Conclusions AECBS could effectively reduce bioburden and improve reprocessing quality of gastroscopes and colonoscopes. AECBS has the potential to replace manual brushing and lower the risk of endoscopy-associated infections, providing a new option for the optimization of reprocessing.